City as Habitat; Assembling the Fragile City - Francis O. Okeke; Ibem O. Eziyi; Clifford A. Udeh; Emmanuel C. Ezema (Civil Engineering Journal, 2020)
The African continent is urbanizing at a breakneck pace and our cities are in a state of crisis. The causes may vary, so also is the degree of severity, but there is a widely felt sense of urban problems requiring urgent solutions. The nature of the problems is complex, with economic, social, educational, political and physical factors playing major roles in exacerbating the situation. Yet, whatever is perceived to be the most serious physical problems in a city, one key underlying question always present is: What can be done about the disaffection of people for their own urban environments? This issue of fragility may be seen in simple terms of a drop in the perceived desirability of the city as a place one can to live, work or shop in. Whatever the name, the fact is that too many Nigerian cities are becoming unattractive to many citizens and residents. This paper aims at identifying the various ways of assembling a fragile city. Through the review of existing literature, the paper highlights the causes of city fragility focusing on three Nigerian cities. It also discusses fragility as the main hurdle to implementing Sustainable Development Goals and how fragile situation birth architecture of fear. Then, it concludes by noting that developing nations in sub-Saharan Africa, including Nigeria need to be proactive in deconstructing their fragile cities.